Tunneled Pleural Catheters for Patients With Chronic Pleural Infection and Nonexpandable Lung. Issue 2 (April 2019) - Majid, Adnan; de Lima, Andres; Parikh, Mihir; Chee, Alex; Fernandez-Bussy, Sebastian; Kheir, Fayez
Abstract : Chronic pleural infection is characterized by thickened pleura and nonexpandable lung often requiring definitive surgical intervention, such as decortication and/or pleural obliteration procedures. Such procedures are associated with significant morbidity and require proper patient selection for a successful outcome. We report a cohort of 11 patients with pleural space infection and a nonexpandable lung treated with tunneled pleural catheters (TPCs). Following placement, hospital discharge and TPC removal occurred after a median of 5 and 36 days, respectively. Three patients presented with residual loculated effusion that resolved with instillation of intrapleural fibrinolytic therapy. One patient eventually required open window thoracostomy for ongoing pleural infection due to poor medical compliance with TPC care and drainage instructions. TPCs represent an alternative option for drainage of an infected pleural space in nonsurgical candidates with a nonexpandable lung. Their use, as a compliment to traditional treatment, may facilitate prompt hospital discharge and ambulatory management in patients with limited life expectancy.